Implementasi Pendidikan Inklusi dalam Membentuk Keterampilan Sosial Anak Berkebutuhan Khusus di SD Negeri Karanganyar Gunung 02 - Ardelin, Ananda Putri; Sunarso, Ali (YASIN, 2025)
Inclusive education is a fundamental framework that provides equal opportunities for children with special needs (CSN) to develop social skills. This study aims to analyze the implementation of inclusive education at SDN Karanganyar Gunung 02 in fostering CSN's social skills, covering the teaching process, the influence of inclusive education on social skills, and the challenges encountered. A qualitative approach with descriptive methods was utilized to collect data from teachers and the school principal and documentation, validated through source and technique triangulation. The findings show that inclusive education at this school successfully enhances CSN's confidence, empathy, and communication skills through empathy-based learning, peer tutoring, and positive reinforcement. An inclusive environment and personalized teaching strategies also support CSN's active participation in group activities. However, significant challenges such as communication barriers, low concentration levels, and insufficient teacher training remain obstacles. This study highlights the importance of collaboration among teachers, parents, and relevant stakeholders in creating an inclusive environment that holistically supports CSN development.